Perjuangan Hak Atas Permukiman dan Kawasan Hutan Lindung Kelurahan Gading Sari Kecamatan Kundur - Salko, Elvin Yofinda; Rahmawati, Nanik; Syafitri, Rahma (CV Insan Kreasi Media, 2023)
The phenomenon of land conflict is one of the problems that often occurs in society. Land is a basic human need for life so that every human being tries to own and control it. One of the land conflicts that occurred was the conflict over a protected forest area which only had forest and the main function of protection but in reality, the designation of a protected forest area in Gading Sari Village was a residential area, public facilities, community cultivated land and not a natural forest. The fact that forests cannot be separated from human elements such as the presence of local communities who have lived in the area for generations. Even before there were state regulations, the context of forest areas had to be placed in the mindset of spatial planning and interactions between elements. This condition worries the local community for the ownership they have, the overlapping regulations experienced by the community make the community still have to defend their right to housing for survival. Meanwhile, the government is trying to keep implementing policies, which in this case is to protect protected forest areas according to their functions. The purpose of this study was to find out how the struggle for rights to settlements and protected forest areas in the Gading Sari Village, Kundur District, used Pierre Bourdieu's Social Practice theory. The method used in this study is a qualitative method with as many as 12 informants and uses data collection techniques and tools in the form of observation, interviews, and documentation. The results of the study found that the habitus owned by the community is understood that the Gading Sari Village is not owned by anyone, but the rules that have been issued by the government as symbolic capital will change the community's habitus and make the Gading Sari Village an arena of struggle with various capitals owned. The community is trying to maintain their settlements, but on the other hand the government is also trying to keep implementing the rules by issuing new policies that are adapted to the conditions of the community.